2020
DOI: 10.1177/0146167220968612
|View full text |Cite
|
Sign up to set email alerts
|

Leaving the Loners Alone: Dispositional Preference for Solitude Evokes Ostracism

Abstract: What are the interpersonal consequences of seeking solitude? Leading theories in developmental research have proposed that having a general preference for solitude may incur significant interpersonal costs, but empirical studies are still lacking. In five studies (total N = 1,823), we tested whether target individuals with a higher preference for solitude were at greater risk for ostracism, a common, yet extremely negative, experience. In studies using self-reported experiences (Study 1) and perceptions of oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 87 publications
0
20
1
Order By: Relevance
“…This is important, considering that laypeople readily infer personality or individual characteristics from a target's solitude preferences. For example, past work has shown that a solitude seeking target is judged to be cold, introverted, and unlikeable (Ren & Evans, 2021;. Deviating from these lay beliefs, the current research shows that valuing time alone is not necessarily linked to, and may even have nothing to do with, an individual's personality.…”
Section: Discussioncontrasting
confidence: 46%
See 1 more Smart Citation
“…This is important, considering that laypeople readily infer personality or individual characteristics from a target's solitude preferences. For example, past work has shown that a solitude seeking target is judged to be cold, introverted, and unlikeable (Ren & Evans, 2021;. Deviating from these lay beliefs, the current research shows that valuing time alone is not necessarily linked to, and may even have nothing to do with, an individual's personality.…”
Section: Discussioncontrasting
confidence: 46%
“…Deviating from these lay beliefs, the current research shows that valuing time alone is not necessarily linked to, and may even have nothing to do with, an individual's personality. This discrepancy adds to our understanding of common misconceptions of solitude seeking, and the potential consequences of expressing an appreciation of time alone (Ren & Evans, 2021;Ren, Stavrova, & Evans, 2022).…”
Section: Discussionmentioning
confidence: 92%
“…On a related note, even though participants were more willing to ostracize a low than a high self-control target, the overall level of ostracism intentions was low (2.34 on a 7-point scale). The reluctance to engage in ostracism has been reported in other studies using similar measures and can be potentially explained by inclusion (rather than exclusion) being the most common behavior in social interactions (Ren & Evans, 2020;Rudert & Greifeneder, 2016).…”
Section: Discussionmentioning
confidence: 60%
“…To illustrate how local SAM works, we utilize publicly available real world data (N = 790) from a recent social psychology experiment investigating the effects of perceived preference for A SAM APPROACH TO SEM 9 solitude on intentions to ostracize others (Ren & Evans, 2021). We describe aspects of the study relevant for illustrating the SAM function and refer readers to Ren and Evans (2021) for further details of the study. Participants were randomly assigned to form an impression about a (hypothetical) target person with either low or high preference for solitude ("sol").…”
Section: Example 1: Illustrating the Steps Of The Local Sam Proceduresmentioning
confidence: 99%